A study of prevalence of HCV/HIV Co-Infection in a Tertiary Health Care Centre in Punjab - Sanjay Goyal; R.P.S. Sibia; Vikas Sharma; Anjali Chawla; Ajay Pal; Mallika Jain; Aarzoo Chawla (GMC Patiala Journal of Research and Medical Education, 2019)
Background: Coinfection with HIV and HCV is common since both infections share similar routes of transmission. Co-infection with hepatitis C virus and human immunodeficiency virus is common in certain populations. Among HCV (+) persons, 10% are also HIV (+), and among HIV (+) persons, 25% are also HCV (+). Many studies have shown that in intravenous drug users, coinfection prevalence can be as high as 90%-95%. There is increasing evidence supporting the concept that people infected with HIV have a much more rapid course of their hepatitis C infection. Treatment of co-infection is often challenging because highly active anti-retroviral therapy (HAART) is frequently hepatotoxic, especially in the presence of HCV. The purpose of this review is to describe the effects that HIV has on hepatitis C and the treatment options in this challenging population. This article shows the prevalence of Hepatitis C in HIV patients reported to Government Medical College/ Rajindra Hospital, Patiala. Methods: 4924 HIV positive patients registered under ART centre of GMC / Rajindra Hospital Patiala from 1 October, 2018 to 30th September, 201 st 9 were included in this study. HCV positive cases were detected by Elisa IgM and HCV RNA detection. Results: Out of 4924 HIV patients screened for HCV, 673(13.66%) patients were positive for HCV. Out of which 473(70.28%) were males and 200(29.7%) were females. Age distribution was done among these reactive patients and it was found that maximum number of HCV and HIV co-infected patients (383) were among the age group of 20 -40 years, which was 56.9% of total HCV and HIV co- reactive patients. Conclusion: HCV infection is common in HIV reactive patients. This coinfection is important due to common modes of infection in these two populations and prognostically due to early and rapid progression of liver disease in these patients.